Design of an ehd pump for microfluids application - Chua, S.N (Universiti Malaysia Sarawak, UNIMAS, 2010)
This project is about studies of ion-drag EHD micropump and to design a readyto-fabricate improved design. The study mainly focuses on the factors that can improve the pumping performance of the micropump. This report started with the studies of theoretical aspect of microfluidics which are related to micropump system and then the principle of the ion-drag EHD pumping. The fabrication methods of micropump are elaborated which to find the cost effective and technically validated fabrication. Parylene and SU-8 will be the main choice of the material due to its cheap and easy to fabricate advantages, to form the skeletal structure of the micropump. Gold is used as electrode of its good conductivity, low residual stress and ease of deposition. A synthesis of comparison results of pumping performance of ion-drag micropump from a few previous testing by other researchers is conducted. The comparisons showed that electrode designs, electrode pair gap and channel height played the main important roles of improving the pumping performance, and they are all related with backflow effect of electric-fluidic field. The final design of the ion-drag micropump is a parallel electrodes micropump, with proposed improvement by valving structure to reduce backflow effect.